Proceedings of 6th Eurasphalt &Amp; Eurobitume Congress 2016
DOI: 10.14311/ee.2016.234
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation and behavior of microsurfacing with recycled materials

Abstract: Road networks play a vital role in the development of country's economy. It is necessary to develop new technologies to improve the performance and safety of the roads. Added to that, it is necessary to enhance the evolution of the roadways over time in terms of maintaining its surface while respecting the challenges of sustainable development. Microsurfacing is one of the techniques used to satisfy these challenges. However, there is very little information on the evolution and behavior of the product on shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The most popular for the use in emulsion still remains the hydrochloric acid (НСl). For its part, bitumen as per technological method of productioncan be used as oxidized or distilled (Zulu et al, 2018;Broughton et al, 2012;Labi et al, 2007;Yu et al, 2017;Watson and Jared, 1998;Smith and Beatty, 1999;Arbia et al, 2016;Robati et al, 2013;Giorgi et al, 2016;Mahmoud et al, 2015;Hwan et al, 2015). But for this technology, distillation bitumen from heavy highresinous, low-paraffinic oil, usually from Venezuelan fields is optimal (Giorgi Claude et al, 2016;Pyshyev et al, 2015;Sidun et al, 2021).The topic of using oxidized bitumens in slurry surfacing technologies causes interest both among the producers and the scientists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The most popular for the use in emulsion still remains the hydrochloric acid (НСl). For its part, bitumen as per technological method of productioncan be used as oxidized or distilled (Zulu et al, 2018;Broughton et al, 2012;Labi et al, 2007;Yu et al, 2017;Watson and Jared, 1998;Smith and Beatty, 1999;Arbia et al, 2016;Robati et al, 2013;Giorgi et al, 2016;Mahmoud et al, 2015;Hwan et al, 2015). But for this technology, distillation bitumen from heavy highresinous, low-paraffinic oil, usually from Venezuelan fields is optimal (Giorgi Claude et al, 2016;Pyshyev et al, 2015;Sidun et al, 2021).The topic of using oxidized bitumens in slurry surfacing technologies causes interest both among the producers and the scientists.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies observed that any amount of RAP from 0 to 100% can be used in the mixture while the recommended amount of RAS to be added to the mixture is 17%. Furthermore 90% of RAP and 10% of RAS can be added to the micro-surfacing mixture while still be within the limits specified by ISSA guidelines [27,28]. Micro-surfacing has a quick set time thereby allowing opening to traffic in 1 hour or less [3].…”
Section: Benefitsmentioning
confidence: 99%
“…In the mix design stage, a cohesion test is used to determine the minimum mineral filler content. However, other than the mineral filler content, several other factors also contribute to the strength evolution in the microsurfacing mix, as shown in Figure 1 (11)(12)(13)(14)(15)(16)(17). A study on fillermastic interaction by Robati et al (6) pointed out that the rate of cohesion development was higher for a higher pH of filler, a higher zeta potential, and a higher methylene blue value.…”
Section: Introductionmentioning
confidence: 99%